Ethnomedicinal practice of Tinospora cordifolia (Willd.) Meirs ex Hook f. & Thoms. by the traditional medicine practitioners at Savar, Dhaka (Jahangirnagar University Journal of Biological Sciences, 2016)
Abstract not availableJahangirnagar University J. Biol. Sci. 4(2): 47-51, 2015 (December)